2018
DOI: 10.14256/jce.1678.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fly-ash based geopolymer coated aggregate on bituminous mixtures

Abstract: Effect of fly-ash based geopolymer coated aggregate on bituminous mixturesThe research presented in the paper is conducted to evaluate properties of fly ashbased geopolymer coated aggregates and their effect on characteristics of bituminous mixtures. The investigation included aggregate testing, scanning electron microscope (SEM) analysis of fly ash and fly ash-based geopolymer, Marshall mix design, indirect tension test, dynamic shear rheometer (DSR) test for rheology, and repeated load test on bituminous mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The surface morphology and microstructure changes in all modified binders were observed and analyzed using the NOVA NANOSEM 230 equipment as shown in Fig 3 . The Scanning Electron Microscope (SEM) utilizes signals resulting from interactions between electrons and the sample to visualize and analyze various aspects, including the external morphology (texture), chemical composition, crystalline structure, and material orientation within the samples. This powerful imaging technique provides valuable insights into the microscopic properties of materials [19].…”
Section: Test Methodsmentioning
confidence: 99%
“…The surface morphology and microstructure changes in all modified binders were observed and analyzed using the NOVA NANOSEM 230 equipment as shown in Fig 3 . The Scanning Electron Microscope (SEM) utilizes signals resulting from interactions between electrons and the sample to visualize and analyze various aspects, including the external morphology (texture), chemical composition, crystalline structure, and material orientation within the samples. This powerful imaging technique provides valuable insights into the microscopic properties of materials [19].…”
Section: Test Methodsmentioning
confidence: 99%
“…In addition, Dayal et al, [3] found that the incorporating of fly ash geopolymer affect the complex shear modulus of asphalt binder. Furthermore, the result showed that the rutting factor on modified asphalt binder also increased compare to virgin asphalt binder.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the result showed that the rutting factor on modified asphalt binder also increased compare to virgin asphalt binder. Dayal et al, [3] also stated that the bituminous mixtures containing fly ash geopolymer show better resistance to permanent deformation, which points to their higher potential rutting resistance and longer fatigue life. Thus, the addition of fly ash geopolymer into the asphalt mixture is expected to decrease the rate of rutting due to the increase in softening point [4][5].…”
Section: Introductionmentioning
confidence: 99%